An Approach to Terminology Teaching. A Methodological Proposal Adapted to the Training Needs of Translators - Schnell, Bettina; Rodríguez, Nadia (Íkala, Revista de Lenguaje y Cultura, 2010)
The aim of this article is to provide methodological reflections about learning and teaching terminology in the context of translator training. These reflections are based on the premise that the professional reality determines what we teach and how we teach, that is to say, the type of terminological and terminographic competences future translators should acquire and the training methodology we should adopt in order to develop these competences. We outline the contextual framework in which terminology training for translators is situated and we address the relation between terminology and specialized translation, taking a closer look at the concept of terminological competence on the basis of Cabré's and Alcina's approaches. The article concludes with a methodological proposal focused on the learning process. Recieved: 29-01-2010 / Accepted: 28-04-2010 How to reference this article: Schnell, B. & Rodríguez, N. (2010). Aproximación a la enseñanza de la terminología. Una propuesta metodológica, adaptada a las necesidades formativas de los traductores. Íkala, 15(3), 181 – 203.